2012
DOI: 10.1002/pd.3992
|View full text |Cite
|
Sign up to set email alerts
|

Cortical maturation in fetuses referred for ‘isolated’ mild ventriculomegaly: a longitudinal ultrasound assessment

Abstract: Objectives To compare cortical maturation between fetuses with isolated mild ventriculomegaly (IMV) and healthy fetuses, and to explore its potential prognostic value in IMV.Methods This prospective study quantified cortical maturation by ultrasound in 24 fetuses with IMV and 46 healthy fetuses. Depth and grading the developmental pattern of the parieto-occipital fissure (POF), calcarine fissure (CF) and sylvian fissure, and grading the Sylvian fissure operculization at 23-25, 27-28 and 31-32 weeks gestation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…On this regard, we demonstrated that calcarine sulcus was less deep in the hemisphere contralateral to ventricular dilation in those cases with unilateral dilation. Changes in parieto‐occipital and calcarine sulci have been previously related with ventricular enlargement, although the mechanism behind is still controversial . Decreased sulci depth could be related with a mechanical deformation due to ventricular dilation or may indicate an underdeveloped maturation due to altered neuronal proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On this regard, we demonstrated that calcarine sulcus was less deep in the hemisphere contralateral to ventricular dilation in those cases with unilateral dilation. Changes in parieto‐occipital and calcarine sulci have been previously related with ventricular enlargement, although the mechanism behind is still controversial . Decreased sulci depth could be related with a mechanical deformation due to ventricular dilation or may indicate an underdeveloped maturation due to altered neuronal proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of appearance of sulci in a nonselected population of mild fetal VM has shown significant delay of 2 weeks in MRI, being the absence of specific sulci associated with poorer prognosis . Regarding ultrasonography evaluation, an inverse relationship between ventricle size and calcarine depth that correlated to cases with later progression has been described . However, these studies did not quantify cortical maturation or only included few sulci in their evaluation missing other brain regions that could be also affected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies using three‐dimensional US have shown that fetuses with CHD have smaller intracranial volumes and increased cerebral blood flow perfusion . Recent reports have suggested that routine two‐dimensional US could quantitatively assess fetal cortex maturation in terms of brain fissure depths . If this method could be used in fetuses with CHD, then the detection of cerebral maturation impairment in routine obstetrical scans would be simplified, and close prenatal follow‐up could be implemented.…”
Section: Introductionmentioning
confidence: 99%